Dichloroacetate Stabilizes Mitochondrial Fusion Dynamics in Models of Neurodegeneration - O’Hara, Darren; Davis, Gavin M.; Adlesic, Natalie A.; Hayes, Jerrard M.; Davey, Gavin P. (Frontiers in Molecular Neuroscience, 2019)
Abstract: Mitochondrial dysfunction is a recognized hallmark of neurodegenerative diseases and abnormal mitochondrial fusion-fission dynamics have been implicated in the pathogenesis of Parkinson’s disease (PD). This study characterizes the effects of metabolic flux inhibitors and activators on mitochondrial fusion dynamics in the parkinsonian cell culture model of differentiated PC12 cells. Using a real time confocal microscopy assay, it was found that the carnitine palmitoyltransferase I (CPTI) inhibitor, etomoxir, reduced mitochondrial fusion dynamics in a time-dependent manner. Etomoxir also decreased JO2, m and ROS production rates. The mitochondrial pyruvate carrier (MPC) inhibitor, UK5099, reduced fusion dynamics and in combination with etomoxir these inhibitory effects were amplified. Use of the pyruvate dehydrogenase (PDH) kinase inhibitor dichloroacetate, which is known to increase metabolic flux through PDH, reversed the etomoxir-induced effects on fusion dynamics, JO2, m but not ROS production rates. Dichloroacetate also partially reversed inhibition of mitochondrial fusion dynamics caused by the parkinsonian-inducing neurotoxin, MPP+. These results suggest that dichloroacetate-induced activation of metabolic flux in the mitochondrion may be a mechanism to restore normal mitochondrial fusion-fission dynamics in metabolically challenged cells.